Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-73 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Natural standing of the SCI patient at school following 12 months of therapy (A). After 18 months of CDT she stands straighter during working in the kitchen (B). The patient prefers to be bare foot (B) or to wear socks to have more input from the soles of the feet for better balance because of the damage of the fasciculus gracilis.